Reparation ecology and climate risk in Latin-America: Experiences from four countries - Lampis, Andrea; Brink, Ebba; Carrasco-Torrontegui, Amaya; dos Santos, Agni Hévea; Solórzano-Lemus, Estuardo; Vásquez-Arango, Claudia (Frontiers in Climate, 2022)
IPCC’s Sixth Assessment is a landmark in recognising social justice and local knowledge as imperative for successful climate adaptation; however, taking this new scientific consensus seriously has profound implications. While narratives of fossil fuel companies and closing climate windows often dominate climate politics, there is an urgent need for new thinking frames, especially given that everyday adaptations by the most vulnerable are often hindered by incumbent actors at more local scales. In response, this paper tackles the issue of climate risk and human well-being in Latin America from an emerging and innovative perspective: reparation ecology. Reparation is a heuristic category by means of which we systematise converging evidence about the responses of local Latin-American communities to severe socio-environmental crises that are closely connected to climate risks and to long-lasting threats to the well-being of human societies and ecosystems. The results focus on a comparative analysis of five case studies on nature-based urban adaptation in two low-income settlements in Brazil; local ecological governance led by actors from the organised civil society in Colombia; agroecological and just innovative food production systems in Ecuador and sustainable urban-rural food markets in Guatemala. Assuming the complexity of climate change from a culturally and geographically located perspective, the paper unveils the non-doomed ecologically reparative character of these initiatives. It therefore contributes to the recent turn in the debate on climate risk, claiming that diverse groups of people and communities around the world are contributing to radical change, tuning their behaviours and social arrangements in what an emerging scholarship defines as reparation ecology.